Satellite-assisted irrigation using the FAO-56 dual method: Scope and limitations - Paz-Pellat, Fernando; Bolaños-González, Martín Alejandro (Tecnología y ciencias del agua, 2022)
The estimation of water requirements of crops using the FAO-56 dual method needs a robust and reliable parameterization of the crop coefficient (Kc). The use of remote sensing through vegetation indices (VI) to define a relationship with Kc is a task that requires an understanding of the scope and limitations of each. This paper sets the perspective about estimates based on VI relative to those based on Kc, noting that the latter is rather limited for not considering soil water content. Using the KIMO SAVI index and its application to two experiments (maize and wheat) with evapotranspiration measurements using lysimeters, the relationship of this index with Kc is analyzed aiming to establish a methodology for a solid parametrization of the relationships between these two approaches, using the beginning and end of the crop development stages with an expo-linear growth model. The relationships obtained in this parameterization yielded a good fit (R2 >0.96).